(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study investigates the relationship between work-life balance (WLB) and job performance, as well as the impact of WLB on employee engagement within the automobile industry. Utilizing a quantitative research design, data were collected from a sample of 300 employees through structured questionnaires featuring Likert-scale items that measured perceptions of WLB, job performance, and employee engagement. The analysis employed descriptive statistics to summarize the data and one-sample t-tests to evaluate the proposed hypotheses. Findings reveal a significant positive relationship between work-life balance and job performance, indicating that employees who effectively manage their professional and personal responsibilities exhibit higher productivity, better work quality, increased efficiency, and fewer errors. Additionally, the study confirms that work-life balance positively influences employee engagement, enhancing commitment, enthusiasm, motivation, and willingness to go the extra mile. These results underscore the critical importance of fostering a supportive work environment that promotes work-life balance to achieve superior job performance and heightened employee engagement. The implications suggest that organizations within the automobile industry should implement comprehensive WLB initiatives to cultivate a more motivated and productive workforce, thereby driving long-term organizational success. Future research is recommended to explore longitudinal effects and incorporate qualitative methods for a deeper understanding of individual experiences with work-life balance